PERAN GURU DALAM MEMANFAATKAN TEKNOLOGI DALAM PEMBELAJARAN DARING - Siti Solia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This research was carried out during the Covid 19 pandemic. Learning activities during the Covid 19 period must continue, so that learning objectives can still be achieved. Therefore, this study aims to determine the role of teachers in utilizing technology in online learning during the Covid 19 period. Especially in the online learning process by using technology as a learning medium at SD Islam Al-Azhar 10 Serang City, the supporting and inhibiting factors for online learning activities. by using technology as a learning medium at SD Islam Al Azhar 10 Serang City, the output of online learning by utilizing technology as a learning medium at SD Islam Al Azhar 10 Serang City. The approach and research method used is descriptive qualitative. Through data collection techniques such as interviews, observations and documentation using the Miles and Huberman data analysis model consisting of the data collection process, data reduction, data presentation, and verification/drawing conclusions. The results of the study show that the role of teachers in utilizing technology in online learning is very important in the success of this online learning process, especially at this time online learning is dependent on technology and internet networks. This is proven through the results of interviews that have been carried out directly with teachers regarding their role in the online learning process.